2012
DOI: 10.1155/2012/294587
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and Innate Immune Responsiveness toBorrelia burgdorferi sensu latoin Exposed Asymptomatic Children and Children with Previous Clinical Lyme Borreliosis

Abstract: Why some individuals develop clinical manifestations in Lyme borreliosis (LB) while others remain asymptomatic is largely unknown. Therefore, we wanted to investigate adaptive and innate immune responsiveness to Borrelia burgdorferi sensu lato in exposed Borrelia-antibody-positive asymptomatic children (n = 20), children with previous clinical LB (n = 24), and controls (n = 20). Blood samples were analyzed for Borrelia-specific interferon (IFN)-γ, interleukin (IL)-4, and IL-17 secretion by ELISPOT and Borrelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…The overall conclusion, that elevated numbers of SFCs are associated with a previous contact with the Borrelia bacterium , however, was confirmed and could not be linked to symptomology nor to the degree of recovery or to antibiotic treatment. Elevated IFN‐γ levels among asymptomatic individuals and previous LB patients have also been found by others .…”
Section: Discussionsupporting
confidence: 73%
“…The overall conclusion, that elevated numbers of SFCs are associated with a previous contact with the Borrelia bacterium , however, was confirmed and could not be linked to symptomology nor to the degree of recovery or to antibiotic treatment. Elevated IFN‐γ levels among asymptomatic individuals and previous LB patients have also been found by others .…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, children and adults have different immune responses to B. burgdorferi: in adults, the immune response is characterized by a strong Th1 response with high numbers of B. burgdorferi-specific interferon (INF)-g-secreting cells and low levels of interleukin (IL)-4, whereas children seem to have a more balanced immune response with elevated secretion of both IFN-g and IL-4. 10…”
Section: Asymptomatic B Burgdorferi Infectionmentioning
confidence: 99%
“…Lyme meningitis (LM) is diagnosed in about 2% of children with Lyme disease, 10 and has a 13% prevalence among all forms of aseptic meningitis diagnosed in a borreliosis-endemic region during the peak period of Lyme disease. 30 Like aseptic meningitis, LM is characterized by signs and symptoms that are quite similar to those observed in the case of viral meningitis.…”
Section: Neuroborreliosismentioning
confidence: 99%
“…It is thought to play an important role in the pathogenesis of rheumatoid and osteoarthritis (40); however, it is also an important regulator of host defense through granulopoiesis and neutrophil recruitment (41). Several studies have proposed that IL-17 may play a role in neuroborreliosis and Lyme arthritis in humans (19,20), although this remains controversial (17,18). Using a murine vaccination and challenge model system, others have found that IL-17 directly impacts Lyme arthritis development (22).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the correlation between B. burgdorferi exposure and IL-17 production is not as clear. Stimulation of peripheral blood mononuclear cells (PBMC) from normal donors did not induce IL-17 production (17), and no serum IL-17 could be detected in B. burgdorferi antibody-positive asymptomatic children (18). In contrast, IL-17 can be found in the cerebrospinal fluid of neuroborreliosis patients (19) and synovial T cells produce IL-17 in response to stimulation with the neutrophil-activating protein A (NapA) of B. burgdorferi (20).…”
mentioning
confidence: 99%